Does a brief trial of endotracheal CPAP before extubation increase the work of breathing in preterm infants?. (June 2021) - Vervenioti, Aggeliki; Dassios, Theodore; Sinopidis, Xenophon; Dimitriou, Gabriel
Abstract: A brief period of endotracheal continuous positive airway pressure (ETT-CPAP) can predict extubation outcome but longer periods are associated with increased work of breathing and extubation failure. In ventilated preterm infants, brief ETT-CPAP does not increase the work of breathing and can be used to predict the outcome of extubation. Highlights: A brief period of endotracheal continuous positive airway pressure (ETT-CPAP) can predict extubation outcome in preterms. ETT-CPAP could potentially increase the work of breathing. ETT-CPAP before extubation does not increase the work of breathing compared to low rate synchronised mechanical ventilation.